Diagnosis, Management and Pathophysiology of Polycystic Ovarian Syndrome: Review Article (Journal of Pharma Insights and Research, 2026)
Polycystic Ovarian Syndrome (PCOS) is a pervasive endocrine disturbance affecting approximately 8% to 13% of women in their reproductive prime, characterized by a heterogeneous constellation of hyperandrogenism, ovulatory dysfunction, and distinct ovarian morphology. The condition occurs due to multiple factors like polygenic susceptibility and environmental triggers, leading to a state of chronic low-grade inflammation and metabolic disarray. Central to its development are the synergistic effects of neuroendocrine irregularities, specifically increased gonadotropin-releasing hormone pulse frequency, and peripheral insulin resistance. These mechanisms cause ovarian theca cell hyperplasia and excessive androgen synthesis, which in turn arrest follicular maturation and precipitate the characteristic polycystic appearance. Apart from its reproductive implications, the syndrome acts as a significant risk factor for type 2 diabetes mellitus, cardiovascular disease, and endometrial neoplasia. Diagnosis necessitated by the Rotterdam criteria requires the exclusion of mimicking pathologies such as congenital adrenal hyperplasia and hyperprolactinemia. Management strategies have transitioned from purely symptomatic relief toward holistic models that prioritize aggressive lifestyle modification alongside targeted pharmacological interventions. The combination of insulin sensitizers, anti-androgens, and newer metabolic agents like GLP-1 receptor agonists reflects an evolving therapeutic paradigm aimed at mitigating long-term systemic complications. Early identification and a multi-disciplinary healthcare remain paramount in improving the metabolic and psychological trajectory of affected individuals throughout their lifespan.